Energy regeneration from vehicle unidirectional suspension system by a non-contact piezo-magneto harvester. (10th March 2021) - Alhumaid, Saleh; Hess, Daniel; Guldiken, Rasim
Abstract: Potential energy is wasted from vehicle vibration caused by road roughness. The suspension system absorbs vibration and dissipates energy in the form of heat. The dissipated energy can be recaptured into useful energy to enhance electric vehicles efficiency. This paper proposes a dual-mass unidirectional shock absorber with a piezoelectric harvester to assess the potential power that can be harvested from vibration. The regenerative suspension can be divided into two parts: transmission module and conversion module. The components of the transmission model are rack and pinion, bevel gears, planetary gearbox, shaft, and overrunning clutch that make the harvester rotates in one direction. The conventional electromagnetic model is replaced by a conversion model that consists of piezoelectric plates that are excited by magnetic forces induced by rectangular magnetic plates that are uniformly placed on an internal ring rotator and concentric external ring stator. A mathematical model is built to describe the process and calculate the power output resulting from the piezoelectric plates. The theoretical results illustrate a root mean square of output power of 16 W and 242 W can be achieved with a ring radius of 0.05 m with vehicle speed 120 km/h on good road condition and poor road condition, respectively.